Unconscious Processing of Negative Animals and Objects: Role of the Amygdala Revealed by fMRI - Fang, Zhiyong; Li, Han; Chen, Gang; Yang, JiongJiong (Frontiers in Human Neuroscience, 2016)
Previous studies have shown that emotional stimuli can be processed through the amygdala without conscious awareness. The amygdala is also involved in processing animate and social information. However, it is unclear whether different categories of pictures (e.g., animals, objects) elicit different activity in the amygdale and other regions without conscious awareness. The objective of this study was to explore whether the factors of category, emotion and picture context modulate brain activation for unconscious processing. Pictures denoting different nonhuman animals and objects in negative and neutral emotional valences were presented using a sandwich-masking paradigm. Half of them were presented with human-related information in the contexts, and half were not. Our results showed significant interaction among category, emotion and context in the amygdala and subcortical regions. Specifically, negative animals elicited stronger activation in these regions than negative objects, especially with human contexts. In addition, there were different correlation patterns between the amygdala and cortical regions according to whether they included human context. There were limited activations in cortical category-related networks. These results suggest that the amygdala and subcortical regions dominantly process negative animals, and contextual information modulates their activities, making threatening stimuli that are most relevant to human survival preferentially processed without conscious awareness.